A Typology Study And Factors Affecting Land Conversion In Dukuhwaluh Village, Kembaran Sub-District, Banyumas - Ayundasari, Cantika Diffa; Suwarsito, Suwarsito; Sarjanti, Esti (Prosiding University Research Colloquium, 2021)
This study aimed to determine the number of land conversions, the factors affecting land conversion, and the typology of land conversion. This is a descriptive study applying field research that aimed at obtaining primary and secondary data. The population covered 12 people owner of agricultural land. This sampling technique employed the snowball method. The data required were primary and secondary data. Data analysis used descriptive qualitative to describe the analysis of land conversion, the factors affecting it, and the typology of land conversion. The results revealed that there was a change in land conversion in Dukuhwaluh Village of 26,094 Ha or 14,235%. The most dominant land conversion was residential land which increased to 12,518 Ha, and mixed garden land was reduced to 3,985 Ha, and irrigated paddy land was reduced to 9,062 Ha. There were 2 factors affecting land conversion; internal and external factors. Internal factors were the community did not rely on agricultural land as a source of income, agricultural products met the needs of life, the landowners decided to convert his land because of his own decision. External factors were the foundation offered high prices to buyers. The typology was patterned systematic conversion, land conversion in response to population growth, multi-form or amorphous conversion.